1998
DOI: 10.1152/jn.1998.79.3.1494
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Effects of Bicuculline: Modulation of an Allodynia-Like State by an A1-Receptor Agonist, Morphine, and an NMDA-Receptor Antagonist

Abstract: Single-unit recordings were made in the intact anesthetized rat of the responses of dorsal horn neurons to C-, Adelta-, and Abeta-fiber stimulation. The postdischarge and windup responses of the same cells along with responses to innocuous stimuli, prod and brush, also were measured. The effects of (-)-bicuculline-methobromide (0.5, 5, 50, and 250 microg) were observed on these neuronal responses. The C- and Adelta-fiber-evoked responses were facilitated significantly in a dose-dependent manner. The input was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 76 publications
3
22
0
Order By: Relevance
“…These data suggest that morphine most likely inhibits the response of dorsal horn projection neurons by augmentation of the GABAergic and glycinergic inputs. Consistent with our finding, it has been shown that the effects of spinally applied morphine on lumbar wide-dynamic-range neurons are largely attenuated by spinal bicuculline (Reeve et al, 1998). Notably, the inhibitory effect of morphine on dorsal horn projection neurons was attenuated to a greater extent by bicuculline than strychnine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest that morphine most likely inhibits the response of dorsal horn projection neurons by augmentation of the GABAergic and glycinergic inputs. Consistent with our finding, it has been shown that the effects of spinally applied morphine on lumbar wide-dynamic-range neurons are largely attenuated by spinal bicuculline (Reeve et al, 1998). Notably, the inhibitory effect of morphine on dorsal horn projection neurons was attenuated to a greater extent by bicuculline than strychnine.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that 10 M morphine produces a near maximal inhibition of voltage-gated calcium channels in dorsal root ganglion neurons (Wu et al, 2004) and hyperpolarization of lamina II neurons in spinal cord slices (Yoshimura and North, 1983). The similar dose of morphine also inhibits wide-dynamic-range neurons in the lumbar spinal cord in vivo (Reeve et al, 1998). Furthermore, the inhibitory effect on dorsal horn projection neurons by topical 10 M morphine (see Results) is similar to the inhibition achieved by intravenous 2.5 mg/kg morphine Chen et al, 2005), which produces analgesia in conscious rats (Chen and Pan, 2001).…”
Section: Role Of Spinal Opioid Receptors In the Effect Of Topicalmentioning
confidence: 92%
“…In line with such idea, we found that blockade of GABA A or glycine receptors induced selective static or dynamic mechanical allodynia, respectively. Accordingly, in vivo electrophysiological studies have consistently demonstrated that bicuculline has no effect on low-threshold responses of dorsal horn neurons, but increases A␦ fibermediated mechanical responses (Reeve et al, 1998;Kontinen et al, 2001;Seagrove et al, 2004). Finally, our results are also consistent with findings in a rat model of spinal nerve ligation in which selective chemical ablation of superficial dorsal horn neurons expressing the NK1 receptor did not alter electrophysiological response of dorsal horn neurons to brushing of the skin (Suzuki et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Spinal application of the GABA A -receptor (GABA A R) antagonist bicuculline leads to a robust disinhibition of adult rat dorsal horn neurons and a reduction in cutaneous mechanical thresholds (Cronin et al 2004;Ishikawa et al 2000;Reeve et al 1998;Sivilotti and Woolf 1994). Newborn dorsal horn cells have lower mechanical thresholds and larger receptive fields than those in the adult (Andrews and Fitzgerald 1994;Fitzgerald 1985;Holmberg and Schouenborg 1996;Torsney and Fitzgerald 2002), which could result from a delayed maturation of inhibitory circuits in the neonatal dorsal horn.…”
Section: Introductionmentioning
confidence: 99%